1.3: Advanced Optical Safeguarding of Automotive Camera Monitor Systems. (26th August 2021) - Axmann, B.; Langner, F.; Vogelmann, M.; Bauer, J.; Blankenbach, K.
Abstract : Camera monitor systems (CMS) become, not only for automotive, more and more important. Lifesaving applications require as well highest safety criteria such as image quality, non‐erroneous reproduction and latency free transmission. We report on new methods to verify the optical output of the CMS display toward the newly introduced "light‐to‐light" supervision.